New treatments for levodopa‐induced motor complications. Issue 11 (21st August 2015) - Rascol, Olivier; Perez‐Lloret, Santiago; Ferreira, Joaquim J
Abstract: Levodopa (l ‐dopa)‐induced motor complications, including motor fluctuations and dyskinesia, affect almost all patients with Parkinson's disease (PD) at some point during the disease course, with relevant implications in global health status. Various dopaminergic and nondopaminergic pharmacological approaches as well as more invasive strategies including devices and functional surgery are available to manage such complications. In spite of undisputable improvements during the last decades, many patients remain significantly disabled, and a fully satisfying management ofl ‐dopa–induced motor complications is still an important unmet need of PD therapy. This article reviews the recent trial results published from 2013 to April 2015 about pharmacological and nonpharmacological interventions to treat motor complications. Randomized controlled trials conducted in patients suffering from already established complications showed that new levodopa (l ‐dopa) formulations such as intrajejunall ‐dopa–carbidopa infusion and bilayered extended‐releasel ‐dopa–carbidopa (IPX066) can improve motor fluctuations. Positive results were also obtained with a new monoamine oxidase B (MAO‐B) inhibitor (safinamide) and a catechol‐O‐methyltransferase COMT inhibitor (opicapone). Pilot data suggest that new formulations of dopamine agonists (inhaled apomorphine) are also of potential interest. The development of novel nondopaminergic adenosine A2A antagonists (istradefylline, preladenant, and tozadenant) to treat motor fluctuations showed conflicting results in phase 2 and phase 3 trials. For dyskinesia, trials with new amantadine extended‐release formulations confirmed the interest of the glutamatergic N ‐methyl‐d ‐aspartate (NMDA) antagonist approach. Positive pilot antidyskinetic effects were also recently reported using serotonin agents such as eltoprazine and glutamate mGluR5 modulators such as mavoglurant. However, the translation to clinical practice of such innovative concepts remains challenging, because subsequent phase 2 trials conducted to confirm the antidyskynetic effects of mavoglurant failed, leading to the interruption of the development of this compound for this indication. © 2015 International Parkinson and Movement Disorder Society